Expression and Purification of Hybrid LL-37Tα1 Peptide in Pichia pastoris and Evaluation of Its Immunomodulatory and Anti-inflammatory Activities by LPS Neutralization - Ahmad, Baseer; Hanif, Quratulain; Xubiao, Wei; Lulu, Zhang; Shahid, Muhammad; Dayong, Si; Rijun, Zhang (Frontiers in Immunology, 2019)
This study pertains to the new approach for the development of hybrid peptide LL-37Tα1 and its biomedical applications. A linear cationic hybrid peptide, LL-37Tα1 was derived from two parental peptides (LL-37 and Tα1) recognized as potent anti-endotoxin without any hemolytic or cytotoxic activity. We successfully cloned the gene of hybrid peptide LL-37Tα1 in PpICZαA vector and expressed in the P. pastoris. The recombinant peptide was purified by Ni-affinity column and reverse-phase high performance liquid chromatography (RP-HPLC) with an estimated molecular mass of 3.9 kDa as determined by SDS-PAGE and mass spectrometry. We analyzed the LPS neutralization by limulus amebocyte lysate (LAL) activity and the results indicate that the hybrid peptide LL-37Tα1 directly binds endotoxin and significantly (p < 0.05) neutralizes the effect of LPS in a dose-dependent manner. Lactate dehydrogenase (LDH) assay revealed that LL-37Tα1 successfully reduces the LPS-induced cytotoxicity in mouse RAW264.7 macrophages. Moreover, it significantly (p < 0.05) decreased the levels of nitric oxide, proinflammatory cytokines including TNF-α, IL-6, IL-1β, and diminished the number of apoptotic cells in LPS-stimulated mouse RAW264.7 macrophages. Our results suggest that the P. pastoris expression system is cost-effective for commercial production of the immunomodulatory and anti-inflammatory hybrid peptide (IAHP) LL-37Tα1 and the peptide may serve as effective anti-endotoxin/anti-inflammatory agent with minimal cytotoxicity.